Modes of low-pressure dual-frequency (27/2 MHz) discharges in hydrogen - Lisovskiy, V.; Booth, Jean-Paul; Landry, K.; Douai, D.; Cassagne, V.; Yegorenkov, V. (PLASMA SOURCES SCIENCE AND TECHNOLOGY, 2008)
This paper studies the modes of dual-frequency (high-frequency (HF)/low-frequency (LF)) low-pressure discharges. The dual-frequency discharges are shown to burn in one of three possible modes. At small LF voltages the first mode is observed, i.e. the HF discharge perturbed by the LF voltage. The second mode, i.e. the combined discharge, exists in the presence of intense ionization in the sheaths, when the LF voltage exceeds some critical value. The third mode (the LF discharge perturbed by an HF field) is observed when a small HF voltage is applied to the burning LF discharge. The range of parameters within which the first mode of the combined discharge may be extinguished by the LF voltage increase is shown to be limited by the HF discharge extinction curve from the low-pressure side as well as the lowest HF voltage for the transition of the discharge from the first mode to the second one.
Keywords: plasma physics; gas discharge